Daily Contacts Under Quarantine amid Limited Spread of COVID-19 in Taiwan. Issue 5 (2nd September 2020) - Fu, Yang-chih; Lee, Hsuan-Wei
Abstract: The COVID-19 global pandemic has forced governments to adopt strategies to limit the spread of the virus in the first half of 2020. Under comprehensive lockdown and quarantine measures, social life and interpersonal contacts have changed drastically. We explore the extent to which people have adjusted their daily contacts in Taiwan, where the spread of the coronavirus has been minimal and only some potential virus carriers were ordered to quarantine at home. To compare contact patterns across time and between groups, we used longitudinal online surveys and 30-day web-based contact diaries to collect data from a quarantined and a never-quarantined group of people between late March and early May in 2020. Based on individual survey data (N = 298) and diary records (N = 42, 102), we first assess the extent and mode of contacts among all participants against a representative sample of Taiwan that was part of the 2017 module of the International Social Survey Program (ISSP), filtering for age and education to make the groups compatible. Then we evaluate how the daily contacts of the quarantined group (N = 140) differed between shortly before quarantine and during quarantine, and between during quarantine and after quarantine. We also compare between the quarantined group, using only after quarantine data, and the never-quarantined group (N = 158). Preliminary findings indicate some major differences and shed new light on how a contact-based approach to social network studies may help pinpoint precise changes in social interactions under complex circumstances during a pandemic.